The Bet-Hedging Strategies for Seedling Emergence of Calligonum mongolicum to Adapt to the Extreme Desert Environments in Northwestern China - Fan, Baoli; Zhou, Yongfeng; Ma, Quanlin; Yu, Qiushi; Zhao, Changming; Sun, Kun (Frontiers in Plant Science, 2018)
Calligonum mongolicum is a dominant native perennial shrub on active sand dunes in arid deserts of Northern China, and is therefore widely used in sand dune stabilisation in these regions. However, it remains largely unknown about how seedling emergence of C. mongolicum has adapted to unpredictable sand movement and extreme drought. Here we examined effects of sand burial depth, light intensity and seed age on seedling emergence, and consider seed germination and seedling emergence strategies for the shrubs adaption to the desert environment. In our pot experiment, the optimum seeding depth for emergence of C. mongolicum was 2 cm, indicating that for germination and seedling emergence only moderate sand burial is required. Light intensity at the surface soil (0 cm) was important for seedling emergence, while there was no significant difference between 50 and 20 % light flux density, at burial depths of 1 and 2 cm, indicating that C. mongolicum seeds had adapted to sand burial, while not sand erosion. We also found C. mongolicum seedlings emerged in Spring, and also in late Summer to early Autumn. Meanwhile, the final percentage of seedling emergence for 3-year-old seeds, was similar to that of 1-year-old seeds, which meant that C. mongolicum seeds were well conserved under natural conditions in sand dunes, thus were capable of developing a persistent but shallow soil seed-bank. The results indicate that germination and seedling emergence take a bet-hedging strategy to adapt to the extreme desert environment. Our study clarified that the C. mongolicum desert shrub has combined strategies in its adaption to arid sand environments.